From Hyperinsulinemia to Cancer Progression: How Diminishing Glucose Storage Capacity Fuels Insulin Resistance - Irina Kareva (Aging and Cancer, 2024)
ABSTRACT Background Type 2 diabetes (T2D) is a complex metabolic disorder characterized by insulin resistance, hyperglycemia, and hyperinsulinemia. A significant portion of individuals with T2D are unaware of their condition until it has reached advanced stages. T2D is also associated with an increased risk and worse prognosis of cardiovascular disease, cognitive decline, and cancer. Understanding the mechanisms underlying the emergence of insulin resistance is critical for improving early detection and therapeutic interventions. Methods An updated framework is proposed to describe the emergence of insulin resistance that precedes the development of T2D. The model focuses on the impact of diminishing capacity to store excess glucose, which can occur due to a multitude of factors, including age‐related muscle loss. The model is used to simulate responses to oral glucose tolerance tests (OGTTs) to capture the transition from a normal to a diabetic phenotype, as defined by the Kraft criteria. Additionally, the model is used to explore how the metabolic environment influences tumor progression, drawing on experimental data regarding the impact of transient diabetic phenotypes and hyperinsulinemia on cancer therapy efficacy. Results The model successfully demonstrates that reduced glucose storage capacity can qualitatively reproduce the progression from normal to diabetic phenotypes observed in OGTT responses. Furthermore, it shows that tumor progression or regression is highly dependent on the host's metabolic environment, particularly hyperinsulinemia. This aligns with experimental results that connect drug‐induced hyperinsulinemia to a loss of therapeutic efficacy against tumors, whereas the reversal of the diabetic phenotype could restore drug sensitivity and treatment response. Conclusions This study highlights the critical role of hyperinsulinemia, even in normoglycemic individuals, in both the progression of T2D and the modulation of cancer therapy outcomes. Addressing hyperinsulinemia emerges as a promising strategy to enhance cancer treatment efficacy and improve overall health outcomes in patients with or at risk for T2D.